Highly different effects of phage therapy and antibiotic therapy on immunological responses of chickens infected with Salmonella enterica serovar Typhimurium - Grabowski, Łukasz; Węgrzyn, Grzegorz; Węgrzyn, Alicja; Podlacha, Magdalena (Frontiers in Immunology, 2022)
Abstract The appearance of bacteria resistant to most or even all known antibiotics has become a serious medical problem. One such promising and effective alternative form of therapy may be the use of phages, the administration of which is considered to be safe and highly effective, especially in animals with drug-resistant infections. Although there have been no reports to date suggesting that bacteriophages can cause any severe complications or adverse effects, we still know little about their interactions with animal organisms, especially in the context of functioning of the immune system. Therefore, the aim of the present study was, to compare the impact of application of selected bacteriophages and antibiotics (enrofloxacin and colistin), commonly used in veterinary medicine, on immune functions in Salmonella enterica serovar Typhimurium-infected chickens. The birds were infected with S. Typhimurium, and then treated with either phage cocktail, enrofloxacin or colistin for 14 days. The concentrations of a panel of pro-inflammatory cytokines (IL-1β, IL-6, IFN-γ, IL-8 and IL-12) and cytokines that reveal anti-inflammatory effects (IL-10 and IL-4), the percentage of lymphocytes, as well as the level of stress hormones (corticosterone and cortisol), which significantly modulate the immune responses, were determined in different variants of the experiment. The phage cocktail revealed anti-inflammatory effects, when administered either one day after infection or two days after S. Typhimurium detection in feces, as measured by inhibition of the increase in levels of inflammatory response markers (IL-1β, IL-6, IFN-γ, IL-8, and IL-12). This was also confirmed by increased levels of cytokines that exert anti-inflammatory action (IL-10 and IL-4) following phage therapy. Moreover, phages did not cause a negative effect on the number and activity of lymphocytes’ subpopulations crucial for normal immune system function. These results indicate for the first time that phage therapy is not only effective but also can be used in veterinary medicine without disturbing immune homeostasis, expressed as cytokine imbalance, disturbed percentage of key immune cell subpopulations, and stress axis hyperactivity, which were observed in our experiments as adverse effects accompanying the antibiotic therapy.